(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s generation, most people, especially women, are users of cosmetic products; some are using cosmetic products to boost their confidence, while others use cosmetic products for other personal reasons. Cosmetic product usage is the practice of maintaining and enhancing one’s physical appearance with various cosmetic products, including creams, lotions, and others; these products are easily accessible to users here in the Philippines through various distributors. This study aimed to determine the significant relationship between cosmetic product usage and self-esteem among Psychology Students of Bestlink College of the Philippines. The results found that the frequency of using cosmetic products and reasons for using them have a very strong correlation, having a Pearson R-value of 0.9182. It also supports the claims of Aquino J., Balanyos L., Botardo M., Mandanas K., Monte L., and Ordas E. (2017) that personal reasons for choosing what cosmetics to wear lie in their own decision. Women can wear cosmetics to gain self-esteem; however, choosing when and why will dictate that and give self-esteem to the users. This revealed that there are reasons that drive respondents to use cosmetic products that affect their self-esteem, such as when they wear cosmetics, they feel more confident to interact with others, and regularly, when using cosmetics, boosts their self-assurance in social circumstances. It demonstrates that cosmetic products can increase self-esteem when used, considering why it was used because it depends on their own decision and can be dictated by other factors. Ultimately, this study can help minority students gain self-esteem by using cosmetic products appropriate for their age, sex, and any other reasons.